Ghana : Poverty Reduction Strategy Paper. (IMF Staff Country Reports; Country Report ;, 2006)
Ghana's current socio-economic development agenda is to attain middle-income status. The emphasis is on changing the structure of the economy by developing the private sector, diversifying the export base, and increasing agricultural productivity and rural incomes. The importance is on the implementation of growth-inducing policies and programs that have the potential to support wealth creation and sustainable poverty reduction. The priorities include continued macroeconomic stability, accelerated private sector-led growth, vigorous human resource development, good governance, and civic responsibility in a decentralized democratic environment.